2011
DOI: 10.3748/wjg.v17.i13.1766
|View full text |Cite
|
Sign up to set email alerts
|

EUS for choosing best endoscopic treatment of mesenchymal tumors of upper gastrointestinal tract

Abstract: EUS is an effective means of diagnosis for upper GIMTs and is an important tool in choosing the endoscopic therapy for GIMTs, by which the lesions can be treated safely and effectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Although jumbo biopsy and endoscopic submucosal resection may increase the surface area of the tissue sample, they do not significantly increase the depth ( 29 ), and there are procedural risks and complications such as perforation and hemorrhage ( 30 ). In contrast to EUS-FNA, endoscopic submucosal resection is more costly and GLP usually has a thickened epithelium which may limit the use of bite-on-bite technique ( 10 , 31 ). EUS-FNA biopsy can accept partial submucosal lesions and surrounding metastatic tissue purposely, which significantly improves the biopsy positive rate of GLP ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although jumbo biopsy and endoscopic submucosal resection may increase the surface area of the tissue sample, they do not significantly increase the depth ( 29 ), and there are procedural risks and complications such as perforation and hemorrhage ( 30 ). In contrast to EUS-FNA, endoscopic submucosal resection is more costly and GLP usually has a thickened epithelium which may limit the use of bite-on-bite technique ( 10 , 31 ). EUS-FNA biopsy can accept partial submucosal lesions and surrounding metastatic tissue purposely, which significantly improves the biopsy positive rate of GLP ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, tissue sampling is necessary to establish a conclusive diagnosis. Endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) biopsy has evolved to become a leading method to confirm the diagnosis of the pre-therapeutic evaluation in patients suspected of submucosal tumors of the upper gastrointestinal tract ( 10 , 11 ). However, its importance for the diagnosis of GLP has been reported only by description of isolated cases ( 12 ), no systematic study has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…A previous EUS is mandatory to confirm the subepithelial position of lesions, and the possibility of ER 23 . EUS alone, even with a diagnostic algorithm based on EUS findings, 24 cannot substitute for the histological diagnosis to determine the exact histological subtypes and potential malignant behavior of gastric SLS 1 .…”
Section: Discussionmentioning
confidence: 99%
“…22 A previous EUS is mandatory to confirm the subepithelial position of lesions, and the possibility of ER. 23 EUS alone, even with a diagnostic algorithm based on EUS findings, 24 cannot substitute for the histological diagnosis to determine the exact histological subtypes and potential malignant behavior of gastric SLS. 1 EUS concordance is particularly poor for lesions inside the third EUS layer and the interest of FNA or FNB for SLS is also limited with an accuracy ranging from 52% to 89% for EUS FNA 6,25 and from 55% to 71% for EUS FNB 6,26 in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic ultrasound (EUS) is a reliable nonsurgical technique for diagnosis and staging of gastrointesti nal malignancies. The EUS examination has become an integral part of the pretherapeutic evaluation in patients suspected of submucosal tumors of the upper gastrointestinal tract [5,6] . EUS can be used to ascertain the echogenicity, location, size, and depth of lesions and perigastric lymph nodes that are the diagnostic criteria for GLP or gastric lymphoma [4,7] .…”
Section: Introductionmentioning
confidence: 99%